2023
DOI: 10.3389/fcvm.2022.1120085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment of non-alcoholic fatty liver disease on heart failure with preserved ejection fraction

Abstract: In the past few decades, non-alcoholic fatty liver disease (NAFLD) and heart failure with preserved ejection fraction (HFpEF) have become the most common chronic liver disease and the main form of heart failure (HF), respectively. NAFLD is closely associated with HFpEF by sharing common risk factors and/or by boosting systemic inflammation, releasing other secretory factors, and having an expansion of epicardial adipose tissue (EAT). Therefore, the treatments of NAFLD may also affect the development and progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 181 publications
0
2
0
Order By: Relevance
“…Of note, a recent RCT with 73 patients with T2DM and nonalcoholic fatty liver disease (NAFLD) found that pioglitazone improves global longitudinal strain (GLS), and NAFLD is a disease which is associated with an increased risk of developing HFpEF [ 55 ]. Although pioglitazone is recommended for patients with T2DM and NAFLD and based on animal model trials, reduces LV fibrosis, the potential role of this agent in HFpEF needs further investigation, especially because of the increase in the incidence of HF [ 56 ].…”
Section: Thiazolidinediones (Tzds)mentioning
confidence: 99%
“…Of note, a recent RCT with 73 patients with T2DM and nonalcoholic fatty liver disease (NAFLD) found that pioglitazone improves global longitudinal strain (GLS), and NAFLD is a disease which is associated with an increased risk of developing HFpEF [ 55 ]. Although pioglitazone is recommended for patients with T2DM and NAFLD and based on animal model trials, reduces LV fibrosis, the potential role of this agent in HFpEF needs further investigation, especially because of the increase in the incidence of HF [ 56 ].…”
Section: Thiazolidinediones (Tzds)mentioning
confidence: 99%
“…This complex relationship between MASH and cardiovascular morbidity is underscored by shared and interlinked risk factors, including but not limited to IR, T2D, hypertension, dyslipidaemia, metabolic syndrome, and notably, liver fibrosis ( Houghton et al, 2019 ; Ismaiel and Dumitrascu, 2019 ). Furthermore, the relationship between the likelihood of developing cardiovascular abnormalities and the severity of hepatic fibrosis in MASH is strongly correlated ( Yang et al, 2022 ; Wegermann et al, 2023 ).…”
Section: Cardiovascular Complications In Masld/mashmentioning
confidence: 99%
“…The complex link between coronary microvascular dysfunction and HFpEF development in MASH patients is of growing interest. HFpEF, featuring heart failure symptoms alongside normal ejection fraction, is increasingly common in those with metabolic syndrome and MASH, primarily due to diastolic dysfunction and altered filling pressures ( Yang et al, 2022 ; Wegermann et al, 2023 ). This condition constitutes a significant portion of heart failure cases, notably in MASH-related metabolic derangements.…”
Section: Cardiovascular Complications In Masld/mashmentioning
confidence: 99%
“…Recent studies suggested that NAFLD was associated with an increased risk of HF in patients, which may be caused by insulin resistance, impaired glucolipid metabolism, chronic inflammatory activation, increased renin-angiotensin-aldosterone and sympathetic nervous system activity, or the altered expression of adipokines and gut microbiota ( 9 , 10 ). Furthermore, the prevalence of NAFLD in HF patients is progressively increasing ( 11 13 ). However, it is still unclear whether coexisting NAFLD leads to a poorer prognosis in HF patients.…”
Section: Introductionmentioning
confidence: 99%